Clinical estimation of corneal endothelial pump function. - Bourne, W M (1998)
PURPOSE: To develop a technique to estimate the corneal endothelial pump rate in human subjects. METHODS: Corneal hydration control is thought to be maintained by a pump-leak mechanism whereby the leak of solutes and fluid across the endothelial barrier into the stroma is, in the steady state, exactly balanced by the pumping of solutes and passive fluid transfer across the endothelium to the aqueous humor. Overall corneal hydration control can be measured from the rate at which the swollen cornea thins (deswells), and a measure of the leak can be obtained simultaneously from the endothelial permeability to fluorescein. From the pump-leak hypothesis, the deswelling rate is directly proportional to the pump rate and inversely proportional to the leak rate. The relative endothelial pump rate can be estimated as the product of the normalized deswelling rate and the normalized endothelial permeability. This procedure was used to obtain the relative endothelial pump rate in 41 patients with diabetes mellitus, 12 patients with long-term corneal transplants, 20 long-term wearers of contact lenses, and 19 normal volunteer subjects after the short-term administration of topical dorzolamide. RESULTS: The relative endothelial pump rate did not differ significantly from that of control subjects in diabetics, in contact lens wearers, and after dorzolamide administration, but was markedly decreased in the patients with corneal transplants, despite a reduction in permeability (reduced leak). CONCLUSIONS: This method allows the estimation of both the barrier and pump arms of corneal endothelial function and should be useful in the investigation of causes and mechanisms of functional endothelial insufficiency.